The Value of Nasal and Oral Clinical Examination in Febrile Neutropenic Patients for Initiating Antifungal Therapy as a Preemptive Method - Salehi, Mohammadreza; Ghaderkhani, Sara; Sharifian, Ramezan Ali; Dehghan Manshadi, Seyed Ali; Samiee Fard, Elahe; Khodavaisy, Sadegh; Pourahmad, Ramtin; Foroushani, Abbas Rahimi; Rodini, Kamran; Kamali Sarvestani, Hasti (Frontiers in Medicine, 2022)
Background: Invasive fungal infections (IFIs) are complications that lead to mortality and morbidity in hematologic malignancies. The time of starting antifungal therapy is vital. Preemptive antifungal therapy has appeared recently as a new policy for IFIs management based on non-invasive ways in neutropenic patients. Method: We enrolled leukemia patients with neutropenia after chemotherapy in Imam Khomeini Complex. Patients who entered to neutropenic phase were divided into two categories (empirical, preemptive) for receiving antifungal agents. The patients were clinically examined in the preemptive group every day to find IFIs. As soon as clinical evidence of IFIs was observed, antifungal was prescribed. The empiric group patients received antifungals based on the ward protocol. Based on the data in each group the diagnostic and therapeutic results of cases are followed up to three months. Result: We assessed 132 leukemic patients with inclusion and exclusion criteria. Eventually, 80 patients were enrolled. The mean age was 35.52 years. Demographics data and distribution of leukemia type show no significant differences between the two groups. Despite a higher percentage of IFIS discovering in the preemptive group than empirical group (25% vs 18.75% respectively), but data show no significant differences. The average days of IFIs diagnosis since begging of neutropenia in the empiric group were 9.5 days while in the preemptive patients this average was 5.4 days (P-value < 0.001). There were 15 patients with a proven IFI (40% in the empirical and 60% in the preemptive group). Results significantly show the increase in surgical sinus debridement in empirical cases (83.3%) versus preemptive groups (55.5%) (P-value < 0.05). The mortality rate differed significantly among the two groups; the preemptive approach (7.5%) against the empiric group (25%) (p=0.034). Conclusion: Daily oral and nasal cavities examination to find IFIs symptoms and then start preemptive antifungal agents may be able to lead to accurate diagnosis, earlier treatment, and decreasing sinus surgery debridement in leukemia patients with neutropenia.